Reliability and validity of the Brief Attention and Mood Scale of 7 Items: a self-administered, online assessment - Madore, Kevin P.; Osman, Allen M.; Kerlan, Kelsey R.; Schafer, Robert J. (Frontiers in Psychology, 2025)
Changes in technology, regulatory guidance, and COVID-19 have spurred an explosion in online studies in the social and clinical sciences. This surge has led to a need for brief and accessible instruments that are designed and validated specifically for self-administered, online use. Addressing this opportunity, the Brief Attention and Mood Scale of 7 Items (BAMS-7) was developed and validated in six cohorts across four studies to assess real-world attention and mood in one instrument. In Study 1, an exploratory factor analysis was run on responses from an initial nine-item survey in a very large, healthy, adult sample (N = 75,019, ages 18–89 years). Two brief subscales comprising seven items total were defined and further characterized: one for Attention, the other for Mood. Study 2 established convergent validity with existing questionnaires in a separate sample (N = 150). Study 3 demonstrated known-groups validity of each subscale using a large sample (N = 58,411) of participants reporting a lifetime diagnosis of ADHD, anxiety, or depression, alongside the healthy sample of Study 1. The Attention subscale had superior discriminability for ADHD and the Mood subscale for anxiety and depression. Study 4 applied confirmatory factor analysis to data (N = 3,489) from a previously published cognitive training study that used the initial nine-item survey, finding that the Attention and Mood subscales were sensitive to the intervention (compared to an active control) to different degrees. In sum, the psychometric properties and extensive normative data set (N = 75,019 healthy adults) of the BAMS-7 may make it a useful instrument in assessing real-world attention and mood.